2020
DOI: 10.1108/jocm-02-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Love your mistakes!—they help you adapt to change. How do knowledge, collaboration and learning cultures foster organizational intelligence?

Abstract: PurposeThe study aims to determine how the acceptance of mistakes is related to adaptability to change in a broad organizational context. Therefore, it explores how knowledge, collaboration and learning cultures (including “acceptance of mistakes”) might help organizations overcome their resistance to change.Design/methodology/approachThe study used two sample groups: students aged 18–24 years (330 cases) and employees aged >24 years (326 cases), who worked in knowledge-driven organizations. Structural equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 85 publications
6
41
0
Order By: Relevance
“…The adoption of these concepts will require significant changes in several companies; however, it will increase the business continuity and organizational development; the real consequences of the crisis caused by COVID-19 pandemic will only be known in some years; then, sooner companies leaders conduct a critical analysis on their business and recognize “mistakes” and concepts neglected in terms of management, greater will be the chances of survival. This is in line with Kucharska and Bedford (2020). The authors argue that the “acceptance of errors” allows greater adaptability regarding organizational change.…”
Section: Final Considerationssupporting
confidence: 68%
“…The adoption of these concepts will require significant changes in several companies; however, it will increase the business continuity and organizational development; the real consequences of the crisis caused by COVID-19 pandemic will only be known in some years; then, sooner companies leaders conduct a critical analysis on their business and recognize “mistakes” and concepts neglected in terms of management, greater will be the chances of survival. This is in line with Kucharska and Bedford (2020). The authors argue that the “acceptance of errors” allows greater adaptability regarding organizational change.…”
Section: Final Considerationssupporting
confidence: 68%
“…All terms were defined to ensure participant understanding of the questions. To measure mistakes acceptance and change adaptability, participants responded to statements using a 7-point Likert scale (adapted from Kucharska and Bedford, 2020a).…”
Section: Methodsmentioning
confidence: 99%
“…Hind and Koenigsberger (2008) and Thomas and Brown (2011) argue similarly and have also stressed that higher levels of mistakes acceptance foster a learning process that is visible in the effective adoption of inevitable change. Mainga (2017), Kucharska and Bedford (2020a) argue that a consistent learning culture should not comprise just a learning-based environment but should also incorporate the acceptance of mistakes. Based on the outlined scholarship, the following hypothesis has been developed: H1: Acceptance of mistakes influences adaptability to change positively.…”
Section: Organisational Learning and Change Adaptabilitymentioning
confidence: 99%
“…Learning fosters the knowledge development, but a knowledge culture must enhance the positive attitude and motivation among employees to learning routines. Kucharska and Bedford (2020) defined constant learning culture as comprising a learning climate and mistakes acceptance. Hence, it can be concluded that a knowledge culture supports both of learning culture's components.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Constructs, scales statements and their sources Knowledge culture is consisted of all surrounding conditions that support the effective and efficient flow of knowledge throughout the whole organization(Islam et al, 2013(Islam et al, , 2015 All employees perceive knowledge as a value We have a common language to support knowledge exchange We are encouraged to share knowledge, ideas and thoughts We care about quality of knowledge we share(Kucharska and Bedford, 2020) Learning culture "(. .…”
mentioning
confidence: 99%